Foot drop secondary to spinal abscess caused by brucellosis: a case report - Orunoglu, Merdan; Gokoglu, Abdulkerim (Journal of the Pakistan Medical Association, 2025)
Brucellosis is a systemic zoonotic disease with multiple organ involvement, which is caused by an intracellular coccobacillus. The disease is seen worldwide. It is usually transmitted via unpasteurised milk and other dairy products or infected animals. It often involves the musculoskeletal system, mostly the spine. The most common form of osteo-articular involvement in the spine is spondylodiscitis. Spinal abscess caused by the spread of the infection to the epidural space is extremely rare. In addition to antibiotics, early surgical treatment contributes to the patient’s neurological recovery faster. It should be noted that abscess drainage and minimally invasive fusion methods may be required in cases where pyogenic sacroiliitis is observed. An interesting case with drop foot, negative pre-operative Brucella agglutination test and radiological spondylodiscitis accompanied by lumbar spinal abscess and sacroiliitis is presented. Keywords: Brucellosis, Sacroileitis, Spinal epidural abscess.